Efektivitas Penerapan Model Pembelajaran Market Place Activity Berbantuan Aplikasi Canva - Heni Suryani; Agus Samsul Bassar; Syarifah Setiana Ardiati (Prodi PAI IAILM Suryalaya, 2025)
The rapid development of technology in the last few decades has brought significant changes to various fields, one of which is in the field of education. Education in the era of Technology 5.0 faces challenges in integrating increasingly advanced technology into learning, so educators must develop technology-based learning processes, such as developing learning models that are in accordance with the times, but educators at MAN 3 Tasikmalaya have not implemented a special learning model in the market place activity learning model assisted by the Canva application. The purpose of this study was to determine the effectiveness of the market place activity learning model assisted by the Canva application and to determine the difference in increasing student learning motivation in the experimental class and the control class in the subject of aqidah akhlak in class XI MAN 3 Tasikmalaya. This study uses a quantitative approach with the Quasi Experimental method (quasi-experiment) involving two sample groups, namely the experimental group and the control group. This research design uses a pretest and posttest in each group to be studied. The results of the study and data analysis showed that the learning motivation of students in the experimental class and the control class before being given treatment was in the moderate category and after being given treatment, the experimental class' learning motivation increased, namely in the very high category, while the learning motivation of students in the control class was in the high category. There is a significant difference in the increase in students' learning motivation between learning using the market place activity learning model assisted by the Canva application and learning using conventional learning. The application of the market place activity learning model assisted by the Canva application is in the fairly effective category in the subject of aqidah akhlak towards increasing student motivation in class XI MAN 3 Tasikmalaya. It can be concluded that the market place activity learning model assisted by the Canva application is quite effective in increasing student learning motivation and there is a difference in increasing student learning motivation between the experimental class and the control class. For further research, researchers must be more careful in making questions that are in accordance with the predetermined indicators and in recapitulating values ​​according to the assessment rubric.